An Analysis Of Malaysian Fatwa Of Nasopharyngeal And Throat Swab Test For Diagnosis Of Covid 19 During Fast - Irwan Mohd Subri; Nor Eyzawiah Hassan; Siti Asmat Md Arepen (Akademi Fiqh Islami Malaysia (AFHAM), 2024)
In late December 2019, we were thrown with a new pandemic known as COVID-19 caused by SARS-CoV2 virus. The lab confirmation of the disease required samples from respiratory system Samples are taken from nasopharynx and oropharynx using swabs that inserted through nasal cavity and oral cavity respectively. This year, Ramadan is celebrated while the COVID-19 disease is fast spreading across the globe and the diagnostic procedures need to be carried out. It raised the arguments the swab tests cause a Muslim person’s fast to be invalidated. This article will discuss the issue with the consensus of the Muslim scholars based on Islamic and Fatwa guidelines.